Vaxx to the max does an increase in government health spending lead to an increase in vaccination coverage? - Serrano, Ian Jerald J.; Tai, Jiwan S.; Capuno, Joseph J. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
One health objective, vaccination coverage, has saved millions of lives since the discovery of the first vaccine. To determine how governments influence this specific objective, the elasticity of vaccination rates of select Asian developing countries with respect to government health expenditures per capita was studied. To control for endogeneity in government health spending, the democracy levels and the control of corruption scores of the countries were used as instrumental variables. Select Asian developing countries were used in the study for comparability and in order to analyze in particular health and government systems in transition, which can show clearer variations and improvements in healthcare. To estimate the effects of the explanatory variable on the vaccination rates, we utilized variations of panel data fixed effects regression analysis with instrumental variables. The results show that vaccination rates are inelastic with respect to government health expenditures. Furthermore, additional results showed that the presence of diminishing marginal returns resulted to the inelasticity. However, the two variables still had a small positive relationship. Thus, increasing government health expenditures often leads to increases in vaccination rates. Moreover, additional spending will be even more effective with better governance as characterized by targeted and efficient spending and by campaigns in response to vaccine hesitancy. These findings show that greater prioritization in health policies through increased health spending leads to the fulfillment of health objectives, but because of the inelastic relationship, other crucial factors must also be considered.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Developing countries -- Appropriations and expenditures; Vaccination -- Economic aspects -- Developing countries; Medical care, Cost of -- Economic aspects -- Developing countries